Analysing People Perception and Attitude towards the Significance of BA or Business Analytics in Fostering Agility and Performance of Organizations - Ms. Neha Kumari, Nyarik Geyi, Ashok Kumar Purohit, Neeta Deepaware, Amit Srivastav (Journal for ReAttach Therapy and Developmental Diversities, 2022)
Business Analytics (BA) is becoming increasingly popular as a means of improving a company's performance. BA has the potential to influence performance in a variety of ways. It examines how business agility is affected by the quality of the company's knowledge and its capacity to come up with new ideas. In addition, environment turbulence, both technical and market-related, is studied for its moderating effect. Data from almost 30 companies and almost 180 employees at managerial level, was used to test the proposed methodology. Our findings show that a firm's agility can be improved by enhancing the superiority of its data and its measurements to come up with new ideas, which further enhances business performance. Market and technological upheaval both decrease the impact of enterprises' adaptability on their performance, as well, as we point out in our paper.